International survey on growth indices and impacting factors in children with food allergies. Issue 2 (9th November 2018) - Meyer, R.; Wright, K.; Vieira, M. C.; Chong, K. W.; Chatchatee, P.; Vlieg‐Boerstra, B. J.; Groetch, M.; Dominguez‐Ortega, G.; Heath, S.; Lang, A.; Archibald‐Durham, L.; Rao, R.; et al.
Abstract: Background: Elimination diets required for the management of food allergies increase the risk for poor growth in children. Currently, no worldwide data exist on this topic and limited published data exist on the impact of atopic comorbidity, type of allergy and foods eliminated on growth. We therefore set out to perform a worldwide survey on growth and impacting factors in food allergic children. Methods: A prospective growth survey was performed of children (aged 0–16 years) on an elimination diet with confirmed immunoglobulin (Ig)E and non‐IgE mediated food allergies. Data collected included: weight‐for‐age, weight‐for‐height, height‐for‐age, head circumference, body mass index, type of food allergy and eliminated foods, allergic comorbidities and replacement milk/breast milk. Multivariable regression analysis was used to establish factors that affected growth. Results: Data from 430 patients from twelve allergy centres were analysed: median age at diagnosis and data collection was 8 months and 23 months, respectively. Pooled data indicated that 6% were underweight, 9% were stunted, 5% were undernourished and 8% were overweight. Cow's milk elimination lead to a lower weight‐for‐height Z ‐scores than other food eliminations and mixed IgE and non‐IgE mediated allergy had lower height‐for‐age Z ‐scores than IgE mediated allergy. Children with only non‐IgE mediated allergies had lower weight‐for‐height and body mass index. Atopic comorbidities did not impact on growth. Conclusions: Stunting is more common in children with food allergies than low weight. Children particularly at risk of poor growth are those with non‐IgE and mixed IgE and non‐IgE mediated allergies, as well as those with cow's milk allergy.